Natural resource rents: Theoretical clarification - Ragnar Arnason (University of Iceland, Institute of Economic Studies (IoES), 2008)
The concept of natural resource rents is much used in the natural resource economics literature. It is therefore somewhat surprising that in this same literature it is difficult to find a clear definition of the concept. Possibly as a result, the concept is often loosely employed and in some texts it appears to be taken to be virtually synonymous with profits. The paper provides a definition of the concept of natural resource rents that is both unambiguous and in conformance with the more traditional concept of economic. A general expression for natural resource rents is derived as a function of the resource stock level, the rate of resource use and, its properties explored.
Keywords: 330; Economic rents; natural resource rents; natural resource rents and profits; Ökonomische Rente; Rohstoffwirtschaft; Ressourcenökonomik; Theorie